EFEK FEED SUPLEMEN (VITERNA) TERHADAP PENAMPILAN PRODUKSI AYAM PEDAGING FASE FINISHER - Nonok Supartini (BUANA SAINS, 2008)
This research aimed to study the effect of Viterna Usage on woof performing production of the broilers finisher. Items witch used in the research were 80 broilers (female) strain Lohman with age 1 – 42 days. Attempt device that used is complete random device (CRD) that using 5 treatment with 4 restating water/day. Treatment description is P0 control; P1 use viterna 0,5 cc/l drinking water/day; P2 use viterna 1,0 cc/l drinking water/day; P3 use viterna 1,5 cc/l drinking water/day; P4 use viterna 2,0 cc/l drinking water/day. The result showed that the effect feed supplement (viterna) with different dose for each treatment do not give the performing production. Suggestion for further more research about influence of viterna usage to woof consume, body weight accretion and woof conversion at broiler with different dose have use woof mixture until viterna usage at broiler with different dose have use woof mixture until viterna usage more effective